Quaternary History of a Part of the North Eastern Fringe of the Thar Desert, India - Raghav, K S (Annals of Arid Zone, 2016)
An attempt has been made to establish the Quaternary stratigraphic sequence of the north-eastern fringe of the Thar desert. based on the lithological character, physical order of superposition, artefacts and organic/pottery remains. Semi- quantitative study of detrital qartz grains under SEM, and X-ray analysis of minerals have been utilised to reconstruct the environmental evolutional Â history. The studies reveal three sedimentary cycles in the area. Each cycle commenced with a fluvial phase and through a transitional playa stage culminated in an aeolian phase. The dunes of each aeolian phase have their own characteristic features. Oldest dunes are mostly modified. the second phase of dunes are parabolic and obstacle, and the youngest ones are mainly of obstacle, parabolic,longitudinal and barehanoid types. The last mentioned dunes have derived sand from the reactivation of older dunes.